Red blood cell transfusion in patients with traumatic brain injury: a systematic review protocol - Boutin, Amélie; Chassé, Michaël; Shemilt, Michèle; Lauzier, François; Moore, Lynne; Zarychanski, Ryan; Lacroix, Jacques; Fergusson, Dean A; Desjardins, Philippe; Turgeon, Alexis F (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Anemia is a prevalent condition in critically ill patients and red blood cell transfusions are frequent. Although transfusions at low hemoglobin levels have been shown to be associated with equivalent or better outcomes than higher hemoglobin thresholds, clinical equipoise persists in patients with traumatic brain injury considering their susceptibility to secondary cerebral insults such as those from hypoxemia. Methods Our objectives are to estimate the frequency of red blood cell transfusion in patients with traumatic brain injury and to evaluate transfusion thresholds, determinants and outcomes associated with transfusion strategies. We will conduct a systematic review of cohort studies and randomized controlled trials of patients with traumatic brain injury. We will search MEDLINE, Embase, BIOSIS and the Cochrane Library for eligible studies. Two independent reviewers will screen all identified references. Studies including adult patients with traumatic brain injury reporting data on red blood cell transfusions will be eligible. We will collect data on baseline demographics, trauma characteristics, hemoglobin thresholds, blood transfusions and clinical outcomes (mortality, length of stay, complications, and so on). Two independent reviewers will extract data using a standardized form. We will pool cumulative incidences using DerSimonian and Lair random-effect models after a Freeman-Tukey transformation to stabilize variances. We will pool risk ratios or mean differences with random-effect models and Mantel-Haenszel or inverse variance methods in order to evaluate the association between red blood cell transfusion and potential determinants or outcomes. Sensitivity and subgroup analysis according to timing of red blood cell transfusion, traumatic brain injury severity, year of conduction of the study, risk of bias, notably, are planned. Discussion We expect to observe high heterogeneity in the proportion of transfused patients across studies and that the global proportion will be similar to the frequency observed in the general medical critically ill population. Our systematic review will allow us to better describe and understand current transfusion practices in patients with traumatic brain injury, a clinical population in which liberal transfusions are still advocated in the absence of evidence-based data. Systematic review registration PROSPERO: CRD42014007402 .